Decision - Diagnosis: An Introduction to Diagnostic Error and Medical Decision-Making - Emily Ruedinger; Benji Mathews; Andrew Olson (Association of American Medical Colleges, 2016)
Abstract Introduction Despite the importance and ubiquity of the diagnostic process, diagnostic errors are common and costly, with respect to both health care spending and patient morbidity and mortality. Medical educators then have a duty to address diagnostic errors as part of their quality improvement and patient safety curricula. Given these challenges and the existing educational gap, we created a curriculum in diagnostic reasoning and diagnostic error. Methods This 1-hour lecture provides a robust introduction to the topic of diagnostic as well as an opportunity for structured self-reflection about learners' own experience with diagnostic errors. The educational outcomes were developed not only to give learners the knowledge and skills they need to improve the diagnostic process and decrease diagnostic error but also to cultivate and demonstrate attitudes of humility and openness about diagnostic reasoning and error for learners and faculty. Results This work has been presented and evaluated in the standalone format included here and adapted for use during full- and partday workshop sessions. It was well received by learners and effective at improving both internal medicine and pediatric resident knowledge about medical decision-making and cognitive biases. Discussion This educational activity is an important contribution to implementing focused educational interventions about diagnostic error and medical decision-making, and can serve as an introduction for a larger curriculum or as a stand-alone educational activity.